Crime Scene Investigation And Forensic Evidence: Forensic Analysis And Tools (Journal of Pharmaceutical Negative Results, 2023)
Digital forensics tools are all new. Until the early 1990s, much of digital research was done through live analysis, which meant exploring digital media using a questionable device as someone else could. As resources became more complex and filled with more information, live analysis became more complex and inefficient. Eventually, freeware and proprietary technologies began to grow as both computer and software platforms carefully filter, extract, or scan data on the phone without damaging or repairing it. Digital forensics tools can fall into many different categories, some of which include database forensics, disk and data capture, email analysis, file analysis, file viewers, internet analysis, mobile device analysis, network forensics, and subscription analysis. Many tools do more than one task at a time, and the key to digital intelligence tools are “folds” —that involves hundreds of specific technologies with a variety of functionality into one great tool kit. New tools are being developed daily, both as top government-sponsored solutions and lower hacker rigs. Each recipe is slightly different. Some of these go beyond simple search for files or images, and are immersed in the realm of cybersecurity, which requires network analysis or cyber threats. If there is a tool for everything, the most pressing question is which one to use.